USER INTERFACE MEASUREMENT ANALYSIS OF TRAVEL E-COMMERCE BASED ON USABILITY AND USER EXPERIENCE - Komariah, Siti Hajar; Mulyana, Asep; Dewi, Rita Komala; Yunizar, Yunizar (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
Technological developments, especially in Information and Communication Technology (ICT), encourage the growth of new ICT-based businesses with online systems (e-commerce) consisting of Traveloka, Nusatrip, and tiket.com. The User Experience (UX) is influenced by how he feels when interacting with the device in front of him. The application users use to access online stores is the User Interface (UI). The research method used is a quantitative method and confirmation survey with the help of SPSS, and a comparison has been made of measuring UI parameters based on Usability and UI Measurement and analysis in this study used the Webuse tool and Mean Opinion Score method to determine the quality of the three e-commerce UIs in the eyes of their users and what kind of experience they felt when browsing these websites. The novelty is using the new hybrid method Webuse tool and Mean Opinion Score in comparing measurement and analysis of UI, Usability and UX parameters. The results of the Usability UI measurement with the Webuse Tool showed that Traveloka gets a score of 81, Nusatrip 72, and Tiket.com gets a score of 74. Meanwhile, in measuring UX against UI with MOS, Traveloka obtained MOS 4.13, Nusatrip 4.0, and Tiket.com obtained MOS 4.0. Keywords: Travel E-Commerce, User Interface, User Experience, Usability